Raphidascaris (Sprentascaris) lanfrediae sp. nov. (Nematoda: Anisakidae) from the fish Satanoperca jurupari (Osteichthyes: Cichlidae) - Marly de Fátima Carvalho de Melo; Jeannie Nascimento dos Santos; Elane Guerreiro Giese; Everton Gustavo Nunes dos Santos; Cláudia Portes Santos (Memorias do Instituto Oswaldo Cruz, 2011)
Raphidascaris (Sprentascaris) lanfrediae sp. nov. is described from the intestine of the freshwater fish Satanoperca jurupari (Heckel) (Cichlidae) from the Guamá River, state of Pará, Brazil. The prevalence in fish (n = 59) was 27% with intensity of one-124 (mean 16) nematodes per fish. The new species is characterized mainly by the markedly larger size of ventricular appendix in relation to the oesophagus, presence of short male caudal alae, 14-16 subventral pairs of preanal papillae and six pairs of postanal papillae.